Features of Work of Multimedia Journalists and Editors in Converged Editorial Offices - M. N. Kim (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2021)
Today, in the converged editorial office the most popular cadres are multimedia journalists and editors. They know not only technological tools for collecting, storing and distributing information, but also they can create  multimedia products for different media platforms. As our surveys show, modern multimedia journalists and editors must combine two important qualities: the fist, they must be fluent in new technological tools, and the second, they must have the skills to work as journalists in converged editorial offices. For this goal we analyzed the trends of the media market, and also conducted in-depth interviews with current multimedia journalists and editors who use the latest technological tools in their work.The hypothesis is that transprofessionalism will be replaced by an in-depth specialization of journalists. The purpose of this study the features of the work of multimedia journalists and editors to create a multimedia product.Materials and methods. The base of analysis are materials obtained during in-depth interviews with  multimedia journalists and editors of online media. The questionnaire was focused on finding out various aspects of the activities of multimedia journalists and editors when they produce a multimedia product. In the result, we may studed various procedural aspects related to the work of journalists in collecting, processing and analyzing information. Also, the ways and forms of organizing individual and joint work of multimedia editorial staff, and the main professional competencies that multimedia professionals should be mastered in  the media sphere.